Minority protection and section 181 of the Companies Act 1965 / M. Athirathan - M., Athirathan (1998)
The present century has witnessed the immense growth and power of companies registered under the Companies Act. Investment in companies has increased by leaps and bounds and the number of persons holding shares in companies has increased tremendously. Many of these investors are minority shareholders who are vulnerable to oppression, discrimination and prejudicial conduct by the majority shareholders. Company Law, therefore, has a duty to ensure that the minority is adequately protected.